1988
DOI: 10.1182/blood.v71.1.117.bloodjournal711117
|View full text |Cite
|
Sign up to set email alerts
|

Effective salvage therapy for lymphoma with cisplatin in combination with high-dose Ara-C and dexamethasone (DHAP)

Abstract: Ninety patients with progressive recurrent lymphoma were treated with a combination of cisplatin 100 mg/m2 intravenously (IV) by continuous infusion over 24 hours, followed by cytosine arabinoside in two pulses each at a dose of 2 g/m2 given 12 hours apart. Dexamethasone, 40 mg orally or IV, was given on days 1 through 4. Vigorous hydration was reinforced by routine use of mannitol. Treatments were repeated at 3- to 4-week intervals for six to ten courses. Most patients had not achieved complete remission (CR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
89
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 0 publications
4
89
1
1
Order By: Relevance
“…Myelosuppression was the major toxicity noted in this study, although renal impairment also occurred in a significant number of patients, as two out of 39 patients had severe renal failure. In relapsed HD similar response rates of 47% have been described following DHAP therapy (Velasquez et al , 1988; Rapoport et al , 1993). The second‐generation cisplatin‐containing regimens ESHAP (etoposide, Solu‐Medrol, cytarabine, cisplatin) (Velasquez et al , 1994; Watts et al , 2000) and ASHAP (adriamycin, Solu‐Medrol, high‐dose cytarabine, cisplatin) (Velasquez et al , 1995; Rodriguez et al , 1999) showed major response rates, which were at least as good and exhibited less myelotoxicity.…”
supporting
confidence: 66%
“…Myelosuppression was the major toxicity noted in this study, although renal impairment also occurred in a significant number of patients, as two out of 39 patients had severe renal failure. In relapsed HD similar response rates of 47% have been described following DHAP therapy (Velasquez et al , 1988; Rapoport et al , 1993). The second‐generation cisplatin‐containing regimens ESHAP (etoposide, Solu‐Medrol, cytarabine, cisplatin) (Velasquez et al , 1994; Watts et al , 2000) and ASHAP (adriamycin, Solu‐Medrol, high‐dose cytarabine, cisplatin) (Velasquez et al , 1995; Rodriguez et al , 1999) showed major response rates, which were at least as good and exhibited less myelotoxicity.…”
supporting
confidence: 66%
“…The dexamethasone‐High dose aracytine (cis)platin (DHAP) regimen combining dexamethasone, cisplatin, and cytarabine is one of the most widely used, showing an overall response rate of 50% to 70% and 60% to 85% for, respectively, non‐Hodgkin and Hodgkin lymphoma. Rituximab is usually added to the DHAP regimen leading to higher response rates for patients with CD20 B‐cell lymphoma, and this regimen might provide better results in patients with a given diffuse large B‐cell lymphoma subtype .…”
Section: Introductionmentioning
confidence: 99%
“…However severe toxicities are often reported, requiring discontinuation and adjustment of the treatment. Among them, renal toxicity constitutes a major concern, with various incidences depending on the studies . Renal insufficiency was reported in 20% of patients with relapse or refractory lymphoma and remained persistent in 6.6% of them .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations